Dental Hygienists' and Dentists' Tobacco Cessation Continuing Education Preferences: Application of a Discrete Choice Method. Issue 1 (24th January 2020) - Chaffee, Benjamin W.; Urata, Janelle; Silverstein, Steven; Couch, Elizabeth T.
Abstract: Despite ample opportunity, dental professionals frequently fall short of connecting tobacco‐using patients with effective cessation support, often citing lack of training as a barrier. To inform development of training options, the aim of this study was to quantify the preferences of practicing dental hygienists and dentists in California for continuing dental education (CDE) offerings related to tobacco and patient tobacco cessation. Two statewide surveys of California dental hygienists and dentists were conducted. In addition to providing their own and their practice characteristics, in a discrete choice experiment, participants indicated their preferences between pairs of randomly generated hypothetical tobacco cessation CDE offerings that differed in topic, cost, delivery modality, and duration. Ultimately, 641 dental hygienists (20.5% of the total invited minus those with undeliverable emails, n=3, 129) and 654 dentists (8.5% of the total invited minus those with undeliverable emails, n=7, 669) responded to at least one of the discrete choice items, and their responses were analyzed. The results showed that each CDE attribute was independently associated with preference. Cost and topic were more strongly associated with preference than were delivery modality and duration. Lower cost, shorter duration courses were generally favored. Alternative tobacco products and patient communication were the most popular topics for participating dental hygienists and dentists, respectively. CDE preferences differed according to participant characteristics: live webinars were the least preferred modality for more experienced dental professionals, and shorter courses were not preferred by dentists in non‐urban locations. These findings showed that these dental professionals considered multiple attributes in selecting CDE courses. To reach the broadest audience, CDE providers should offer low‐cost options across a range of delivery modalities, such as full‐day workshops in rural areas and online webinars for earlier career professionals.